What adults with ADHD want to know: A Delphi consensus study on the psychoeducational needs of experts by experience - Christina Seery; Margo Wrigley; Fiona O'Riordan; Ken Kilbride; Jessica Bramham (Wiley, 2022)
Abstract Introduction A lack of knowledge about attention‐deficit/hyperactivity disorder (ADHD) can contribute to feelings of distress and difficulty in seeking and accepting an ADHD diagnosis. The present study uses a Delphi consensus design to investigate the psychoeducational needs of adults with ADHD and the information about ADHD they would like included in digital health interventions for adults with ADHD. Inclusion of perspectives of service users in developing such interventions ensures that they are evidence based and addresses the risks of engagement barriers. Methods The expert panel consisted of 43 adults with ADHD (age range: 23-67 years). Panel members were asked to rate the importance of the proposed topics and provide additional suggestions. Suggested topics and topics that did not achieve consensus were included for ranking in the second round. Results Interquartile ratings were used to determine consensus. A high consensus was achieved in both rounds, with an agreement on 94% of topics in the first round and 98% in the second round. Most topics were rated as important or essential. Conclusions The findings highlighted that adults with ADHD want to learn about many different aspects of ADHD and the importance of considering their perspectives when developing psychosocial interventions. Findings can be applied when creating psychoeducational content for adult ADHD. Patient or Public Contribution Adults with ADHD were recruited to the Delphi panel to use an experts‐by‐experience approach. In doing so, we are engaging service users in the development of a psychoeducational smartphone app. The evaluation of the app will involve interviews with app users. Additionally, the present study was developed and conducted with ADHD Ireland, a charity based in Ireland that advocates for people with ADHD.